Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10533-011-9592-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nitrogen sources and transformations within karst springs using isotope tracers of nitrogen

Abstract: Isotope analyses of nitrate and algae were used to gain better understanding of sources of nitrate to Florida's karst springs and processes affecting nitrate in the Floridan aquifer at multiple scales. In wet years, d 15 N and d 18 O of nitrate ranged from ?3 to ?9% in headwater springs in north Florida, indicating nitrification of soil ammonium as the dominant source. With below normal rainfall, the d 15 N and d 18 O of nitrate were higher in almost all springs (reaching ?20.2 and ?15.3%, respectively) and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…However, several recent studies have found isotopic evidence for denitrification in karstic aquifers, including those in southwestern Illinois, USA (Panno et al, 2001), southern Germany (Einsiedl and Mayer, 2006), and the Floridan Aquifer (Albertin et al, 2011). One feature of karst aquifers that may facilitate denitrification is large difference in hydraulic conductivity, and thus water age and chemistry, between karstic aquifer matrices and conduits.…”
Section: Magnitude and Mechanisms Of Nitrate Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several recent studies have found isotopic evidence for denitrification in karstic aquifers, including those in southwestern Illinois, USA (Panno et al, 2001), southern Germany (Einsiedl and Mayer, 2006), and the Floridan Aquifer (Albertin et al, 2011). One feature of karst aquifers that may facilitate denitrification is large difference in hydraulic conductivity, and thus water age and chemistry, between karstic aquifer matrices and conduits.…”
Section: Magnitude and Mechanisms Of Nitrate Reductionmentioning
confidence: 99%
“…Although insufficient to directly estimate rates of denitrification, coupled enrichment of δ 15 N NO3 and δ 18 O NO3 is now widely used to infer the occurrence of fractionating processes (Burns et al, 2009). Among these are recent studies that suggest denitrification in the Upper Floridan Aquifer and other karst groundwater systems (Panno et al, 2001;Hackley et al, 2007;Albertin et al, 2011). One potential value of dual isotopic measurements is the ability to partition removal into its component processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, research indicated that 0.8 million people in France were threatened by nitrate-polluted drinking water, 0.85 million in the UK, and 2.5 million in Germany [5]. Thus, issues of groundwater quality are gradually attracting more attention from researchers worldwide [2,[6][7]. Subsequently, many scholars carried out large-scale studies on the detection, prevention, and control of nitrogen in groundwater, and the three types of nitrogen-composed elements (nitrate, nitrite, and ammonium nitrogen) have become topics…”
Section: Introductionmentioning
confidence: 99%
“…In many spring runs in Florida, proliferation of epiphytic algae, as well as benthic macroalgae, have been observed concomitantly with declines of SAV communities (Stevenson et al 2004;Frazer et al 2006;Pinowska et al 2007;Stevenson et al 2007;Quinlan et al 2008;Brown et al 2008). Water quality in groundwater discharged from many springs in Florida has shown significant increases in NO x -N concentration, attributed predominantly to fertilizer application and/or wastewater or manure sources in individual spring sheds (Jones et al 1996;Katz 2004;Albertin et al 2012). Odum (1957) reported mean NO x -N concentration of 0.45 mg L -1 for Silver Springs in the 1950s which had risen to over 1 mg L -1 by 2005 (Munch et al 2006;Quinlan et al 2008).…”
Section: Introductionmentioning
confidence: 99%